Electric vehicle conversion: optimisation of parameters in the design process - Vladimir Popović (Tehnički Vjesnik, 2017)
One of the directions for making cleaner and more economic vehicles is to adopt electric vehicle concept. The paper shows current design concepts for electric vehicles worldwide, as well as current sources for supplying vehicles with electric energy. It describes a conversion of one vehicle so that it can be powered by electric motor. The results of tractive and dynamic characteristics calculation and vehicle stability simulation, before and after the conversion, are shown. Obtained results and influential factors are analysed so they can be optimised in order to influence the final characteristics of the converted vehicle. The conclusion is that the complete optimisation process should be performed before the beginning of vehicle conversion in order to avoid undesirable effects, i.e. undesirable characteristics of converted vehicle and high conversion costs.